Timing of Side-Dress Applications of Nitrogen for Corn in Conventional and No-Till Systems - D. W. Sweeney; D. E. Shoup; Dorivar Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2018)
Environmental conditions vary widely in the spring in southeastern Kansas. As a result, much of the N applied prior to corn planting may be lost before the time of maximum plant N uptake. Side-dress or split applications to provide N during rapid growth periods may improve N use efficiency while reducing potential losses to the environment. The objective of this study was to determine the effect of timing of side-dress N fertilization compared with pre-plant N applications for corn grown on a claypan soil.
Keywords: Nitrogen; side-dress; corn; tillage